A patient with generalized myasthenia gravis facing an impending crisis triggered by early fast‐acting treatment. Issue 2 (17th November 2021) - Tamaki, Kana; Nishida, Yoichiro; Sanjo, Nobuo; Yokota, Takanori
Abstract: Background: An aggressive therapeutic strategy used in the early stages of generalized myasthenia gravis (MG), called early fast‐acting treatment (EFT), involves the use of plasmapheresis, intravenous immunoglobulin and/or intravenous high‐dose methylprednisolone (IVMP). The EFT strategy has been proven to have advantages in achieving a treatment goal of MG, minimal manifestations or better with oral prednisolone at a dose of ≤5 mg/day. Case presentation: A 72‐year‐old woman with anti‐acetylcholine receptor antibody‐positive MG underwent EFT. Even a modified IVMP regimen with a reduced dose of just 250 mg/day for 2 days, given after six cycles of plasmapheresis and 10 mg/day of oral prednisolone for 5 days, triggered a severe myasthenic exacerbation. Subsequent intravenous immunoglobulin therapy successfully averted a crisis. Conclusions: Such acute exacerbation after just 250 mg/day of IVMP for 2 days is rare. However, caution is required when using IVMP for EFT of MG, because the risk factors for exacerbation after IVMP use, and the best approach for treating the exacerbation, are not yet known. Abstract : A 72‐year‐old woman with anti‐acetylcholine receptor antibody‐positive generalized myasthenia gravis underwent early fast‐acting treatment. Even a modified intravenous high‐dose methylprednisolone regimen with a reduced dose of just 250 mg/day for 2 days, given after six cycles of plasmapheresis and 10 mg/day of oral prednisolone for 5 days, triggered a severe myasthenic exacerbation. Although subsequent intravenous immunoglobulin therapy successfully averted a crisis, caution is required when using intravenous high‐dose methylprednisolone for early fast‐acting treatment of myasthenia gravis, because the risk factors for exacerbation after intravenous high‐dose methylprednisolone use, and the best approach for treating the exacerbation, are not yet known.